Farmers’ Adaptation to Covid-19 Pandemic in Akwa Ibom State - Jemimah Timothy Ekanem; Godwin Edem Akpan (Turkish Journal of Agriculture: Food Science and Technology)
The study focused on how farming communities cope with the COVID-19 pandemic in Akwa Ibom State. Specifically, how farmers are affected by the pandemic, their coping strategies, contributions of extension service towards their adaptation, and the support they need to better adapt to the pandemic were examined. A multistage sampling procedure was used in selecting 300 respondents across the agricultural zones in the study area. Descriptive statistics were used to analyse data obtained from the respondents through a well-designed questionnaire. The majority of the respondents have experienced limited access to agricultural inputs (87.9%), limited access to the market (79.6%), unavailability of the labour force at critical times of agricultural production and harvesting (68.7%), health risk and fear (72.6%), increased transportation cost (87.4%), unavailability of facemasks and hand sanitizers (89.1%), dwindling and uncertain finances (92.4%). Majority of the farmers asserted that they had to rely more on the radio (87.6%), religious leaders (67.2%), community leaders (65.4%), and extension agents (45.3%) for COVID-19-related information. They depended more on herbs and traditional medications (72.4%) and had to trek long distances to market farm produce and get inputs (69.7%) to cope with the impact of the pandemic. Contributions from extension services reported by the respondents were majorly from text messages and phone calls. The majority of the respondents solicited regular assessment of COVID-19 impacts in their communities to identify other specific challenges and needs of farmers for a better and timely response.